Competition between FLS and DFR regulates the distribution of flavonols and proanthocyanidins in Rubus chingii Hu - Lei, Ting; Huang, Jun; Ruan, Haixiang; Qian, Wei; Fang, Zhou; Gu, Chunyang; Zhang, Niuniu; Liang, Yaxuan; Wang, Ziyun; Gao, Liping; Wang, Yunsheng (Frontiers in Plant Science, 2023)
Rubus chingii Hu is a berry plant of the genus Rubus of the Rosaceae family, which has high nutritional and medicinal value and is rich in flavonoids. Flavonol synthase (FLS) and dihydroflavonol 4-reductase (DFR) compete for the common substrate dihydroflavonols to regulate the metabolic flux of flavonoids. However, the competition between FLS and DFR based on enzyme is rarely reported. Here, we isolated and identified two FLS genes (RcFLS1 and RcFLS2) and one DFR gene (RcDFR) from Rubus chingii Hu. RcFLSs and RcDFR were highly expressed in stems, leaves, and flowers, although the flavonol accumulation in these organs was significantly higher than that of proanthocyanidins (PAs). The recombinant RcFLSs demonstrated bifunctional activities via hydroxylation and desaturation at the C-3α position having a lower Michaelis constant (Km) for dihydroflavonols than RcDFR. We also found that a low concentration of flavonols could significantly inhibit RcDFR activity. To investigate the competitive relationship between RcFLSs and RcDFR, we used a prokaryotic expression system (E. coli) to co-express these proteins. The transgenic cells expressing recombinant proteins were incubated with substrates, and the reaction products were analyzed. Furthermore, two transient expression systems (tobacco leaves and strawberry fruits) and a stable genetic system (Arabidopsis thaliana) were used to co-express these proteins in vivo. The results showed that RcFLS1 was dominant in the competition with RcDFR. Our results demonstrated that the competition between FLS and DFR regulated the metabolic flux distribution of flavonols and PAs, which will be of great significance for the molecular breeding of Rubus plants.